Enhancing MSME Resilience Through Digital Maturity and Dynamic Marketing Capabilities with Business Environment Support - ML Tobing, Wesly Tumbur; Kurniawati, Nidya Oktavia; Rohmania, Aftuqa Sholikatur; Abdullah (JURNAL MANAJEMEN MOTIVASI, 2025)
This study investigates how dynamic marketing capabilities, digital maturity, and environmental support affect MSME resilience in Central Java. Based on data from 150 respondents analyzed using SEM-PLS, findings show that network capability, digital maturity, and environmental support positively influence resilience. In contrast, customer relationship management negatively affects resilience, while founding-team marketing has no significant effect. Digital maturity also weakens some capabilities. Only customer relationship management is moderated by environmental support. Results underscore the interplay of internal capabilities, digitalization, and external support in strengthening MSME resilience.ABSTRAK